Make ‘n’ the subject of the formula if w = (frac{v(2 + cn)}{1 – cn})

A.
(frac{1}{c}(frac{w – 2v}{v + w})) 
B.
(frac{1}{c}(frac{w – 2v}{v – w})) 
C.
(frac{1}{c}(frac{w + 2v}{v – w})) 
D.
(frac{1}{c}(frac{w + 2v}{v + w}))
Correct Answer: Option A
Explanation
w = (frac{v(2 + cn)}{1 – cn})
2v + cnv = w(1 – cn)
2v + cnv = w – cnw
2v – w = cnv – cnw
Multiply through by negative sign
2v + w = cnv + cnw
2v + w = n(cv + cw)
n = (frac{2v + w}{cv + cw})
n = (frac{1}{c}frac{2v + w}{v + w})
Rearrange…
n = (frac{1}{c}frac{w – 2v}{v + w})
There is an explanation video available below.